Hydroxyl directed C-arylation: synthesis of 3-hydroxyflavones and 2-phenyl-3-hydroxy pyran-4-ones under transition-metal free conditions - Paula, Sayantan; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2018)
An efficient, transition-metal free and direct C-arylation of 3-hydroxychromone moieties in the presence of a base, air as an oxidant and arylhydrazines as arylating agents to furnish highly biologically active flavonols or 3-hydroxyflavones has been developed. We have further extended our methodology for the C-arylation of the 5-hydroxy pyran-4-one moiety. The role of the free hydroxyl group towards C-arylation has been delineated.

Hemiketal-keto tautomerism in 2-deoxy-delta-lactones mediated by 2-lithiothiazole in solution state: a formal synthesis of DAH, Kamusol and their C-5 Epimers - Chand, Hemender R.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2019)
The reactions of 2-lithiothiazole on 3,4,6-tri-O-benzyl-2-deoxyglyconolactones have been studied, which resulted in the formation of two products, major (3,4,6-tri-O-benzyl-2-deoxy-1-(2-thiazolyl) glycal) and minor products 3,4,6-tri-O-benzyl-2-deoxy-1-(2-thiazolyl) glycal hemiketal. The hemiketal-keto tautomerism in solution was observed in the minor product. The tautomerism has been studied in various organic solvents and their ratios have been determined by H-1 NMR spectroscopy. The major product from the reaction of 2-lithiothiazole with 2-deoxygluconolactone was utilized for the synthesis of 3-deoxy-D-arabino-2-heptulosonic acid DAH 4 a and 3-deoxy-D-arabino-2-heptulopyranose commonly known natural product kamusol 6 a via acid catalyzed hydration followed by stereoselective methyl glycoside bond formation. Similarly, major product from 2-deoxygalactonolactone furnished 5-epi-DAH 4 b (C-5 epimer of 4 a) and 5-epi-kamusol 6 b (C-5 epimer of 6 a). The minor product has also been utilized for the synthesis of DAH 4 a, 5-epi-DAH 4 b, kamusol 6 a and 5-epi-kamusol 6 b through a common intermediate, alpha-methyl glycosylated product.
Keywords: hemiketals; Ketones; tautomerism; thiazoles; umpolung